1997
DOI: 10.1099/0022-1317-78-12-3161
|View full text |Cite
|
Sign up to set email alerts
|

Beet soil-borne virus RNA 1: genetic analysis enabled by a starting sequence generated with primers to highly conserved helicase-encoding domains.

Abstract: The complete sequence of the 5834 nucleotides of RNA 1 of beet soil-borne furovirus (BSBV, Ahlum isolate) was determined using a PCR product obtained with primers to highly conserved coding regions for helicase-like proteins in RNA 1 of furo-, hordei-and tobraviruses as a starting sequence. Unknown parts of the sequence upstream and downstream of this starting sequence were amplified by means of RT-PCR techniques using combinations of specific and random primers. BSBV RNA 1 contains one large ORF for a readthr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
28
0

Year Published

1998
1998
2009
2009

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(29 citation statements)
references
References 12 publications
1
28
0
Order By: Relevance
“…Because BVQ is extremely difficult to purify, a strategy was adopted for analysing its genome properties which is based partially on previous experiences with BSBV (Koenig, 1997 ;Koenig & Loss, 1997 ;Koenig et al, 1997) and is outlined in Fig. 1.…”
Section: Strategy For Determining the Complete Nucleotide Sequence Ofmentioning
confidence: 99%
See 1 more Smart Citation
“…Because BVQ is extremely difficult to purify, a strategy was adopted for analysing its genome properties which is based partially on previous experiences with BSBV (Koenig, 1997 ;Koenig & Loss, 1997 ;Koenig et al, 1997) and is outlined in Fig. 1.…”
Section: Strategy For Determining the Complete Nucleotide Sequence Ofmentioning
confidence: 99%
“…A starter sequence, which was generated with primers specific for highly conserved helicase-encoding domains in RNA 1 of furo-, pomo-, peclu-, hordei-and tobraviruses (Koenig & Loss, 1997), has enabled the entire nucleotide sequence of the tripartite genome of unpurified BVQ to be determined. This paper describes genome properties of BVQ and compares them with those of other, related viruses.…”
Section: Introductionmentioning
confidence: 99%
“…Originally reported in Italy (Canova, 1959), rhizomania disease is now widespread in most countries where sugar beet is grown (McGrann et al, 2009) and BSBV is often found in beet infected with BNYVV (Meunier et al, 2003). However, the pathogenicity of BSBV and its contribution to the rhizomania syndrome remain unclear, with opinions still divided on this (Prillwitz & Schlösser, 1992;Kaufmann et al, 1993;Lindsten, 1993;Rush & Heidel, 1995).The BSBV genome consists of three single-stranded RNAs of positive polarity, packaged into rod-shaped particles (Koenig et al, 1996(Koenig et al, , 1997Koenig & Loss, 1997). RNA-1 (5.8 kb) encodes the putative viral replicase.…”
mentioning
confidence: 99%
“…The BSBV genome consists of three single-stranded RNAs of positive polarity, packaged into rod-shaped particles (Koenig et al, 1996(Koenig et al, , 1997Koenig & Loss, 1997). RNA-1 (5.8 kb) encodes the putative viral replicase.…”
mentioning
confidence: 99%
See 1 more Smart Citation